Предмет: Алгебра,
автор: Губай
производная от y=ln3x/x^3+5x
Ответы
Автор ответа:
0
1/x^3=x^(-3).
Тогда у=ln3x·x^(-3)+5x.
У'=(ln3x)'·x^(-3)+ln3x·(x^(-3))'+(5x)'=3/(3x)·x^(-3)+ln3x·(-3)x^(-4)+5=x^(-4)-3ln3x·x^(-4)+5=1/x^4 - 3ln3x/x^4 + 5=(1-3ln3x)/x^4+5.
Тогда у=ln3x·x^(-3)+5x.
У'=(ln3x)'·x^(-3)+ln3x·(x^(-3))'+(5x)'=3/(3x)·x^(-3)+ln3x·(-3)x^(-4)+5=x^(-4)-3ln3x·x^(-4)+5=1/x^4 - 3ln3x/x^4 + 5=(1-3ln3x)/x^4+5.
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: География,
автор: coochieman
Предмет: Қазақ тiлi,
автор: musaevaindira18
Предмет: Алгебра,
автор: Аноним